ISL Induces Apoptosis and Autophagy in Hepatocellular Carcinoma via Downregulation of PI3K/AKT/mTOR Pathway in vivo and in vitro - Song L; Luo Y; Li S; Hong M; Wang Q; Chi X; Yang C (Dove Medical Press, 2020)
Lei Song,1,2 Yi Luo,1 Shaoling Li,2 Ming Hong,1 Qi Wang,1 Xiaoling Chi,2 Cong Yang1 1Science and Technology Innovation Center, Guangzhou University of Chinese Medicine, Guangzhou 510405, People’s Republic of China; 2The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong 510006, People’s Republic of ChinaCorrespondence: Cong Yang; Xiaoling ChiScience and Technology Innovation Center, Guangzhou University of Chinese Medicine, Guangzhou 510405, People’s Republic of ChinaTel +86 15625016580Email yangcong303@163.com; chixiaolingqh@163.comAims: Isoliquiritigenin (ISL), a flavonoid from Glycyrrhiza glabra, has previously been reported to have anti-tumor effects in vivo and in vitro. However, the mechanisms whereby ISL exerts its anticancer effects remain poorly understood in hepatocellular carcinoma (HCC).Purpose: In the present study, we investigated the anticancer efficacy and associated mechanisms of ISL in HCC MHCC97-H and SMMC7721 cells.Results: We found that ISL inhibited cell viability and proliferation and induced apoptosis in a dose- and time-dependent manner in liver cancer lines. Furthermore, ISL could activate autophagy in HCC cells, and the autophagy inhibitor HCQ enhances ISL-induced apoptosis in HCC cells. Additionally, ISL induced apoptosis and autophagy through inhibition of the PI3K/Akt/mTOR pathway. Most importantly, in a xenograft tumor model in nude mice, data showed that the administration of ISL decreased tumor growth and concurrently promoted the expression of LC3-II and cleaved-caspase-3. Interestingly, we found that ISL inhibits mTOR by docking onto the ATP-binding pocket of mTOR (ie, it competes with ATP). We thus suggest that mTOR is a potential target for ISL inhibition of hepatocellular carcinoma development, which could be of interest for future investigations.Conclusion: Taken together, the results reveal that ISL effectively inhibited proliferation and induced apoptosis in HCC through autophagy induction in vivo and in vitro, probably via the PI3K/Akt/mTOR pathway. ISL may be a potential therapeutic agent for hepatocellular carcinoma.Keywords: isoliquiritigenin, hepatocellular carcinoma, apoptosis, autophagy, mTOR